Sztuki plastyczne w naiwnych teoriach uczniów edukacji wczesnoszkolnej - Dorota Sobierańska; Aleksandra Szyller (Problemy Wczesnej Edukacji)
From the earliest years, thanks to the interpretation of the observed events and on the basis of social and cultural messages, children have been independently building naive theories of the world referring to concepts from the visual arts fi eld. This article presents the results of my own research. The subject of it was based on third-graders’ statements from Warsaw primary schools concerning the interpretation and description of the term ‘visual arts’. Focus interviews were used to collect qualitative data.